Peningkatan Pemahaman Perjanjian Jual Beli Online yang Dihadapi Bisnis Produk Aromaterapi Di Kota Pekanbaru - Yetti Yetti; Dedy Felandry; Miftahul Haq (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
This activity started from the needed of partners named Asosiasi Pebisnis & Praktisi Produk Aroma Terapi (APPPAT) Riau who do not understand about the aspects of online buying and selling agreement, and the experience that they found about legal issues. Based on description above, it can be concluded the partners can understand the material presented by the team. Some of the problems and couriousity by partner related to the legal issues of online buying and selling and legal issues that they faced can be solved well by the time that activity was held.